The ex-wives murder club - Harrison, Mette Ivie, 1970- (Severn House, 2026)
"What do you do when you realize you married a horrible man? Kill him of course! For Meg (wife #1), Jenny (#2), and Amelia (#3), the term 'a woman scorned' isn't strong enough. They want more than revenge for the years of their life they wasted with their pitiful excuse for a husband. They want him dead. As they carry out their lethal plan, they soon realize they're thinking too small. What about all the other men (and women) who cause immeasurable suffering and get away with it? Thus 'the business' is born. A dazzling new female-owned venture that will change the course of their lives--and shorten many others! And, for Meg and Jenny, it could allow them to experience a love they never thought possible ..."--Provided by publisher.